Dampak Kebijakan Tarif dan Non-tarif Negara-Negara Importir atas Ekspor Tuna Olahan Indonesia - Maharani Tristi; Harianto Harianto; Amzul Rifin (Jurnal Ilmu Pertanian Indonesia, 2021)
This study aims to analyze the impact of the tariff and non-tariff policies implementation of the importing countries on the export performance of Indonesian processed tuna. A cross-sectional gravity model analysis was conducted to find out the impact of these policies on exports. The variables used include GDP per capita of the importing countries, population, economic distance, export prices, actual exchange rates, tariff policies, and non-tariff policies in the form of sanitary and phytosanitary (SPS) and technical barriers to trade (TBT). The estimation shows that the variables of GDP per capita of the importing countries, population, exchange rates, export prices, and SPS give a positive and significant effect on the trade of Indonesian processed tuna commodities. On the other hand, economic distance and TBT policy give a negative and significant impact on the volume of this particular commodity. Meanwhile, the tariff policy implementation also give a negative effect on the export volume, but it is not significant. Keywords: cross sectional gravity, export performance, non-tariffs, tariffs